2020
DOI: 10.11144/javeriana.iyu24.amap
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Muscular Activity and Postural Load During Coffee Harvesting Activities – A Case Study

Abstract: Objective: The goal of this case study was to analyze and evaluate the posture, force and repetitive movement risks associated with manual coffee harvesting activities. Materials and Methods: A self-discomfort report was administered to 28 participants, of whom 4 volunteered for an evaluation of postural load on muscular activity using electromyography and electrogoniometry. Eight upper limb muscles and the kinematics of the wrist and upper arm of the dominant arm were assessed. Results: The results of the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In a study carried out with workers who harvested coffee manually, although it was found that they mainly manifested musculoskeletal discomfort in the lower extremities, when evaluating the intensity of muscle contraction by means of surface electromyography and the measurement of joint angles, it was found that this activity requires considerable physical effort at the level of the upper limbs [42]. A study in Colombian coffee plantations showed that the muscle with the greatest demand was the extensor carpi ulnaris muscle, which is located at the level of the upper extremities; the dynamic activity of this muscle exceeded 20% of the maximum voluntary contraction, making coffee harvesting a threatening activity for the generation of musculoskeletal injuries [43].…”
Section: Risk Factors and Musculoskeletal Lesions In Agricultural Wor...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study carried out with workers who harvested coffee manually, although it was found that they mainly manifested musculoskeletal discomfort in the lower extremities, when evaluating the intensity of muscle contraction by means of surface electromyography and the measurement of joint angles, it was found that this activity requires considerable physical effort at the level of the upper limbs [42]. A study in Colombian coffee plantations showed that the muscle with the greatest demand was the extensor carpi ulnaris muscle, which is located at the level of the upper extremities; the dynamic activity of this muscle exceeded 20% of the maximum voluntary contraction, making coffee harvesting a threatening activity for the generation of musculoskeletal injuries [43].…”
Section: Risk Factors and Musculoskeletal Lesions In Agricultural Wor...mentioning
confidence: 99%
“…The identification of ergonomic risks to which workers are exposed is the first step to improve working conditions, achieving a balance between decent work and economic growth (SDG8). Previous studies in coffee farms show that workers are exposed to biomechanical risk factors and present musculoskeletal discomfort [36,[42][43][44][45][46][47][48], thus, the need arises to carry out a specific evaluation that considers these risk factors. That is why the objective of this research is to identify musculoskeletal symptoms and evaluate ergonomic risk factors in three occupations of a certified coffee farm in Honduras.…”
Section: Risk Factors and Musculoskeletal Lesions In Agricultural Wor...mentioning
confidence: 99%